Quasi-sliding mode control of discrete-time systems - Bartoszewicz, Andrzej (Zielona Góra: Uniwersytet Zielonogórski)
A reaching law approach to the design of discrete-time quasi-sliding mode control systems is considered. First the required position of the system representative point with reference to the sliding plane is specified, and then novel control strategies, which drive the system in such a way that the position actually changes according to the specification, are proposed.
Keywords: sliding-mode control; discrete-time systems